2009
DOI: 10.2337/dc09-1506
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Myocardial Infarction Risk Associated With Diabetes Medications Using Electronic Medical Records

Abstract: OBJECTIVETo assess the ability to identify potential association(s) of diabetes medications with myocardial infarction using usual care clinical data obtained from the electronic medical record.RESEARCH DESIGN AND METHODSWe defined a retrospective cohort of patients (n = 34,253) treated with a sulfonylurea, metformin, rosiglitazone, or pioglitazone in a single academic health care network. All patients were aged >18 years with at least one prescription for one of the medications between 1 January 2000 and 31 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 24 publications
1
69
0
Order By: Relevance
“…Most notably, observational studies using large-scale provider databases in both the UK (29 ) and Canada (30 ) provided early human-based evidence of the protective effect of metformin therapy as well as the increased risk of insulin and sulfonylureas on the development of cancer. More recently, the use of EHR-based research for surveillance purposes was demonstrated to be a useful adjunct to RCTs and provide signals of potential ADE in a study by one of the coauthors of a head-tohead comparison of myocardial infarction risk among users with rosiglitazone vs metformin (31 ). This study demonstrated that EHR-based ADE signal detection systems could have raised early warnings about the excess risk of myocardial infarction associated with rosiglitazone.…”
Section: Ehrs In Diabetes Researchmentioning
confidence: 93%
“…Most notably, observational studies using large-scale provider databases in both the UK (29 ) and Canada (30 ) provided early human-based evidence of the protective effect of metformin therapy as well as the increased risk of insulin and sulfonylureas on the development of cancer. More recently, the use of EHR-based research for surveillance purposes was demonstrated to be a useful adjunct to RCTs and provide signals of potential ADE in a study by one of the coauthors of a head-tohead comparison of myocardial infarction risk among users with rosiglitazone vs metformin (31 ). This study demonstrated that EHR-based ADE signal detection systems could have raised early warnings about the excess risk of myocardial infarction associated with rosiglitazone.…”
Section: Ehrs In Diabetes Researchmentioning
confidence: 93%
“…In particular, the availability of high-throughput information technology solutions for extracting clinical data provides an opportunity to improve the efficiency and conduct of clinical and translational research. [10][11][12] However, electronic data extraction is not without limitations. [13][14][15] Validation of data accuracy and completeness is necessary because data can be missing or incorrect as a result of the data-entry process or of corruption during data transmission, storage, or retrieval.…”
mentioning
confidence: 99%
“…Other industries, such as finance and energy, have embraced data analytics [6], and researchers at Google have shown that an order of magnitude growth in the size of data sets leads to significant improvements in performance of analyses and can overshadow improvements in modeling techniques [7]. Big data have only been reported in a select few epidemiologic studies, such as those linking myocardial infarction and rosiglitazone [8] or rofecoxib [9]. Two significant issues need to be resolved to enable open data mandates: guaranteeing the privacy of study subjects [10] and creating a safe, fair, and open infrastructure for data sharing [4].…”
Section: Open Data: Can It Prevent Research Fraud Promote Reproducibmentioning
confidence: 99%